Bachelor of Science in Nursing; Open & Distance Learning Research Supervision Preparedness: Tutor Perception - Mutowo, Jesca; Chitura, Miriam (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Research Supervision is a process that assists the student to become an independent professional researcher and scholar. In order for that mandate to be met, open and distance (ODL) learning student research supervisors need to have appropriate skills to ensure the academic goal of the University of preparing competent researchers and practitioners is reached. This study sought to establish tutor perceptions on ODL research supervision preparedness. The researchers used a case study for the qualitative methodology. Purposive sampling method was used to select participants from part time tutors who were conducting weekend tutorials. Face to face interviews were conducted using structured interview guides. Generated data was organized into different themes. Common patterns were grouped into significant themes namely: tutor previous experience, training received and methods of supervision. The major findings were that, most part time tutors were not inducted into open and distance learning research supervision and tutors were relying on the experiences gained during their own research studies. This resulted in different formats of the research projects being presented by the ODL students. Although tutors had access to internet facilities and would prefer supervising students on-line, the tutors did not know how to factor in comments for corrections. The study therefore, recommends an ODL research supervision induction/training workshop for tutors. To ensure quality of the final project, a research supervision guideline should be established to guide the tutors and students.